Effect of Internal Technological Defects and Loading Waveform on Structural Composite Fatigue Life - Anastasia Lykova; Dmitriy Lobanov; Alexander Pankov; Mikhail Ugolnikov (Fracture and Structural Integrity)
This paper explores the effect of internal technological defects on the fatigue life of carbon fiber reinforced plastic (CFRP) under simple loading waveforms. One conducted experiments on CFRP specimens with embedded artificial defects, including delamination’s (circular dry-spot) and wrinkling. Following quasi-static tests, one developed a fatigue testing program using triangular and sine waveforms. The findings indicate that these simple waveforms do not significantly affect the fatigue resistance of defect-free CFRP or CFRP with internal technological defects. The presence of the wrinkling defect significantly diminishes the fatigue resistance of CFRP. However, constructing fatigue life curves in relative terms reveals that the reduction in fatigue properties is directly related to a decrease in strength properties. In the case of delamination (dry-spot) defects, a reduction in fatigue life by approximately 2.5 times was observed across the tested range.